2015
DOI: 10.1021/ci500758w
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Methodology of 3D Structure Preparation Influence the Quality of pKa Prediction?

Abstract: The acid dissociation constant is an important molecular property and it can be successfully predicted by Quantitative Structure-Property Relationship (QSPR) models, even for in silico designed molecules. We analyzed how the methodology of in silico 3D structure preparation influences the quality of QSPR models. Specifically, we evaluated and compared QSPR models based on six different 3D structure sources (DTP NCI, Pubchem, Balloon, Frog2, OpenBabel and RDKit) combined with four different types of optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…We then wondered if this accuracy, though unable to reflect suitable changes depending on the nature or position of the substituents, was sufficient to build acceptable QSPR models for prediction. No suitable QSPR models are available for benzoic acids, but such models for aliphatic carboxylic acids have been reported [ 58 , 78 ]. The descriptors used by these QSPR models consist of charges on the atoms of the carboxylic group in both the neutral ( , , , ) and dissociated forms ( , , ).…”
Section: Resultsmentioning
confidence: 99%
“…We then wondered if this accuracy, though unable to reflect suitable changes depending on the nature or position of the substituents, was sufficient to build acceptable QSPR models for prediction. No suitable QSPR models are available for benzoic acids, but such models for aliphatic carboxylic acids have been reported [ 58 , 78 ]. The descriptors used by these QSPR models consist of charges on the atoms of the carboxylic group in both the neutral ( , , , ) and dissociated forms ( , , ).…”
Section: Resultsmentioning
confidence: 99%
“…These approaches can be divided into conformationally-independent, which are based on 2D structure (e.g., Gasteiger’s and Marsili’s PEOE [ 40 , 41 ], GDAC [ 42 ], KCM [ 43 ], DENR [ 44 ]) and conformationally-dependent, calculated from 3D structure (e.g., EEM [ 45 ], QEq [ 46 ] or SQE [ 47 , 48 ]). We would like to highlight that conformationally-dependent charges are considered to be more suitable for chemoinformatics applications [ 1 3 , 7 , 12 , 20 ]. The reason is that these charges contain extensive information not only about chemical surrounding of atoms, i.e., its topology (2D structure based charges) but also geometry and “chemical quality” of the surrounding.…”
Section: Introductionmentioning
confidence: 99%
“…They implemented their methodology as BioShell scripts and concluded that "BioShell combined with the methodology presented in this paper, is crucial in order to predict protein structures while avoiding structural clashes". In yet another work done by Abagyan [13] group, BioShell was used to reconstruct atoms and larger parts of chemical groups missing in protein structures. In this contribution, we present the newest version, rewritten in C++11, which provides widely extended functionality.…”
Section: Introductionmentioning
confidence: 99%